Improving the Nutritional Status of Stunted Toddlers by Utilizing Local Food in Coastal Labu Beach, Deli Serdang Regency - Nurandini, Nabilah; Indirawati, Sri Malem; Putri, Najwa Azlisna; Siregar, Hijriyatun Alhikmah (Universitas Negeri Medan, 2024)
Pantai Labu sub-district is one of the sub-districts located on the coast but has a high number of stunting cases, stunting cases in Paluh Sibaji village are 5 toddlers. Health problems in Paluh Sibaji village have stunting cases that are very concerning even though it has marine potential with protein sources from fish. The village has a variety of abundant fisheries and marine resources. Local food diversity has the potential to be utilised as a source of cheap and easily available nutrition. The village has an abundant variety of fisheries and marine resources. The existence of tamban fish as a local food product has a low selling price and is underutilised as a source of animal protein. This community service aims to utilise local food ingredients as a source of protein for the community. The methods used are atmosphere building, socialisation, community empowerment and the formation of family groups concerned about stunting. This community service activity produced two local food innovations, namely characterised spinach tamban fish balls and moringa leaf tamban fish sticks. Both products are processed from cheap and easily available local raw materials in the village, namely tamban fish and moringa leaves.